Chronic quercetin ingestion and exercise-induced oxidative damage and inflammation - McAnulty, S. R.; McAnulty, L. S.; Nieman, D. C.; Quindry, J. C.; Hosick, P. A.; Hudson, M. H.; Still, L.; Henson, D. A.; Milne, J. L.; Morrow, J. D.; Dumke, C. L.; Utter, A. C.; et al. (Applied Physiology, Nutrition, and Metabolism, 2008)
Abstract: Quercetin is a flavonoid compound that has been demonstrated to be a potent antioxidant in vitro. The objective of this study was to evaluate if quercetin ingestion would increase plasma antioxidant measures and attenuate increases in exercise-induced oxidative damage. Forty athletes were recruited and randomized to quercetin or placebo. Subjects consumed 1000 mg quercetin or placebo each day for 6 weeks before and during 3 d of cycling at 57% work maximum for 3 h. Blood was collected before and immediately after exercise each day, and analyzed for F2-isoprostanes, nitrite, ferric-reducing ability of plasma, trolox equivalent antioxidant capacity, and C-reactive protein. Statistical analyses involved a 2 (treatment) × 6 (times) repeated measures analysis of variance to test main effects. F2-isoprostanes, nitrite, ferric-reducing ability of plasma, trolox equivalent antioxidant capacity, and C-reactive protein were significantly elevated as a result of exercise, but no group effects were found. Despite previous data demonstrating potent antioxidant actions of quercetin in vitro, this study indicates that this effect is absent in vivo and that chronic quercetin ingestion does not exert protection from exercise-induced oxidative stress and inflammation.